Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 617 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "Year is greater than or equal to 2015", "Month is greater than or equal to January", "Country is Australia", "TaxonKey is Passeriformes" ] } The dataset includes 617 records from 5 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000346-150827100048397/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences